PENDAMPINGAN MASYARAKAT MELALUI PROGRAM KEAKSARAAN DI DISTRIK WALELAGAMA, WAMENA KABUPATEN JAYAWIJAYA, PAPUA - paling, sepling; sulendorong, Irsan Hengky; oagay, brigita (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
One of the provinces with the highest illiteracy rate in Indonesia is Papua Province, which is 28.75% of 70.26% in 11 Provinces in Indonesia. Especially in Jayawijaya district, 25.80% of the people are still illiterate. This is due to the extensive geographical conditions, difficult to reach areas, the spread of Papuans that are not evenly distributed in isolated areas. In order to overcome the high rate of illiteracy in Jayawijaya District, especially in the Walelagama District ofWalelagama village, Wamena Christian Teacher Training and Education School as the education practitioner responsible for the quality of education in the Central Papua Mountains carried out literacy assistance programs for the Walelagama village community in Wamena in the District Jayawijaya, Papua. The program was held for 3 months for residents of Walelagama villages aged 15-45 years who had never attended school or dropped out of school. It is hoped that through this assistance, the reading and writing skills of Walelagama residents will be better, so that it can influence the lifestyle of the people in Walelagama village. After literacy assistance, there was a change in the literacy skills of the people studying in the Walelagama village. This was measured from the initial test and the final test given to the study residents before mentoring and after mentoring.